Synergistic co-administration of doxorubicin and berberine by PLGA/PVA hybrid polymeric Nanoformulation for breast cancer treatment - Masoumeh Rahmani; Mahdieh Hemati; Milad Akhlaghi; Bibi Fatemeh Haghiralsadat; Fatemeh Oroojalian (Nanomedicine Journal)
Objective(s): The clinical application of doxorubicin (DOX), a potent anticancer agent, is restricted by its serious side-effects and multidrug resistance. The combination strategy of antineoplastic drugs with Berberine (BBR) as plant-derived natural products enhances the cytotoxicity of chemotherapeutic drugs in cancer cells and also amends their toxicity in normal cells. Materials and Methods: In this study, the nanoparticles (NPs) of PLGA/PVA containing DOX and BBR were synthesized and optimized using the double emulsion-solvent evaporation method. The vesicular size, zeta potential, entrapment efficiency and also the drug release profile was surveyed at different temperatures and pH (37 °C, 7.4 and 42 °C, 5.2). The MTT assay was used to evaluate the cytotoxic effects of individual of DOX and BBR as a free form and as a nanoparticle form and also the combination of DOX- and BBR-loaded NPs on MCF-7 breast cancer cells. Results: The optimum formulation demonstrated that the vesicle size and zeta potential of DOX were 176.4 nm and -56.4 mV and BBR were 150.3 nm and -41.2 mV, respectively. Entrapment efficiency (EE%) for DOX and BBR was 91.0 ± 1.9% and 82.0 ± 1.8%, respectively. The DOX- and BBR -loaded NPs exhibited a sustained and controlled release pattern with the pH- and thermosensitive characteristic. Additionally, the loading of DOX and BBR into PLGA/PVA NPs had a higher toxicity against cancer cells when compared with free forms and the combination of DOX and BBR was exhibited an augmented antineoplastic activity against the cancer cell death. Conclusion: The findings of this study suggest that the coadministration of DOX with BBR using the PLGA/PVA NPs may have the potential clinical application in sensitization cells to DOX and generates synergistic antitumor effects.